Trattamento conservativo della gonartrosi: Platelet Rich Plasma vs acido ialuronico - Cudoni, S.; Zedde, P. (Lo Scalpello - Journal, 2019)
CONSERVATIVE TREATMENT OF GONARTHROSIS: PLATELET RICH PLASMA VERSUS HYALURONIC ACID Osteoarthritis is a degenerative pathology characterised by progressive joint degeneration, which is responsible for the gradual and chronic onset of pain and functional limitations. Owing to its high incidence and frequency in young adults, the treatment of early knee osteoarthritis is currently an important challenge for the orthopaedic surgeon. Over the past 30 years, several techniques have been introduced for the treatment of conservative and non-conservative osteoarthritis, and today the therapeutic possibilities have expanded considerably compared to the past. The aim of this study was to report and compare the clinical and functional results of 60 patients with grade III gonarthrosis according to the Kellgren-Lawrence Classification treated with intra-articular infiltrations of Platelet Rich Plasma (PRP) or hyaluronic acid.